The characteristics of PUFAs-rich virgin fish oil as affected by size of tuna eye - WINI TRILAKSANI; BAMBANG RIYANTO; WAHYU RAMADHAN; FAHRI SINULINGGA; SILVA FAUZIAH (Society for Indonesian Biodiversity, 2023)
Abstract. Trilaksani W, Riyanto B, Ramadhan W, Sinulingga F, Fauziah S. 2023. The characteristics of PUFAs-rich virgin fish oil as affected by size of tuna eye. Biodiversitas 24: 6545-6556. The food supplement market expects growth in demand for long-chain omega-3 fatty acids, particularly Eicosapentaenoic Acid (EPA) and Docosahexaenoic Acid (DHA), which play crucial for brain development and can lower the chances of health issues like depression, Myocardial Infarction (MI), thromboembolism, and cardiac arrhythmias, and have anti-viral effects, boosting the immune system during the pandemic. Therefore, to meet this demand, exploring new sources is crucial. Tuna eyes have emerged as a potential source of DHA; however, quality and standardized sizes pose a challenge as they are by-products. The purpose of this research was to determine how the eye size of tuna affected the quality and yield of fish oil, which is a novel source of omega-3 fatty acids. This study determined the virgin oil profile of tuna eyes, which met the quality standards. The investigation covered morphology, chemical composition, heavy metal content, oil yield and quality, fatty acid composition, and related health lipid indices (Atherogenicity Index (AI) and Thrombogenicity Index (TI)). For the size specifications, tuna eyes were classified into three groups based on their diameter, namely 'small' (<6 cm), 'medium' (6-9 cm), and 'large' (>9 cm). The results showed that eye size directly influenced the weight, fat content, and oil yield, with negligible disparity in chemical composition except for the fat content; the larger the eyes, the higher the oil yield. Tuna eye oil had a safe composition for consumption with low or undetected heavy metals, the oil's oxidative level met CODEX standards, and the fatty acid profile revealed DHA as the most abundant fatty acid, reaching 36.95%. The predominance of n-3 series values in the fatty acid composition of tuna's eye was 9-12 times greater than that of n-6 fatty acid values. The values of AI and TI were 0.33 and 0.12; 0.47 and 0.20; 0.55 and 0.20 for large, small, and medium eyes, respectively. The study highlights tuna eyes' unique characteristics and potential applications in the food supplement industry.